SOSIOLOGI HUKUM UNTUK MEWUJUDKAN HUKUM YANG BERKEADILAN - Umairy, Adib Kamali (HUKMY : Jurnal Hukum, 2023)
Law enforcement in Indonesia tends to prioritize legal certainty only, which is then carried away by the subconscious that truth and justice are written law, our law enforcers are still focused on formal justice, not yet touching on substantive justice. As a result, law enforcement problems are getting worse. So various approaches need to be taken into consideration in the law enforcement process, one of which is the sociological approach to law, because our laws still have a tendency to be firm and rigid towards vulnerable groups, for example the poor, the imbalance between justice and natural loss. Therefore, social facts in society need to be explored more deeply, people's behavior, social phenomena, norms that live in society are something that cannot be ignored if enforcement in Indonesia wants to be serious in ensuring social justice, legal sociology is not for judging good and bad but to provide a description of the facts found. Legal studies on legal sociology try to free judges from the shadow of legal positivism so that they can realize true justice that is felt by society.